Berufliches Crossover zwischen ökonomischer und soziokultureller Fachwelt Eine biografieanalytische Untersuchung - König, Franziska (Qualitative Fall- und Prozessanalysen. Biographie - Interaktion - soziale Welten, 2021)
The change to a different professional world presents employees with new tasks and challenges. Which individual prerequisites must be fulfilled and which institutional framework conditions should be in place for a successful professional crossover? The study shows that the crossover between professional worlds is an overall biographical process that becomes apparent in the biographies of the interviewees even before their professional lives. Successful crossovers are dependend on the hybrid competencies of the individual and are rarely accompanied by institutional and social support services.